Dry and liquid formulations of IBT-V02, a novel multi-component toxoid vaccine, are effective against Staphylococcus aureus isolates from low-to-middle income countries - Wang, Yu; Mukherjee, Ipsita; Venkatasubramaniam, Arundhathi; Dikeman, Dustin; Orlando, Nicholas; Zhang, Jing; Ortines, Roger; Mednikov, Mark; Sherchand, Shardulendra P.; Kanipakala, Tulasikumari; Le, Thao; Shukla, Sanjay; et al. (Frontiers in Immunology, 2024)
Staphylococcus aureus is the leading cause of skin and soft tissue infections (SSTIs) in the U.S. as well as more serious invasive diseases, including bacteremia, sepsis, endocarditis, surgical site infections, osteomyelitis, and pneumonia. These infections are exacerbated by the emergence of antibiotic-resistant clinical isolates such as methicillin-resistant S. aureus (MRSA), highlighting the need for alternatives to antibiotics to treat bacterial infections. We have previously developed a multi-component toxoid vaccine (IBT-V02) in a liquid formulation with efficacy against multiple strains of Staphylococcus aureus prevalent in the industrialized world. However, liquid vaccine formulations are not compatible with the paucity of cold chain storage infrastructure in many low-to-middle income countries (LMICs). Furthermore, whether our IBT-V02 vaccine formulations are protective against S. aureus isolates from LMICs is unknown. To overcome these limitations, we developed lyophilized and spray freeze-dried formulations of IBT-V02 vaccine and demonstrated that both formulations had comparable biophysical attributes as the liquid formulation, including similar levels of toxin neutralizing antibodies and protective efficacy against MRSA infections in murine and rabbit models. To enhance the relevancy of our findings, we then performed a multi-dimensional screen of 83 S. aureus clinical isolates from LMICs (e.g., Democratic Republic of Congo, Palestine, and Cambodia) to rationally down-select strains to test in our in vivo models based on broad expression of IBT-V02 targets (i.e., pore-forming toxins and superantigens). IBT-V02 polyclonal antisera effectively neutralized toxins produced by the S. aureus clinical isolates from LMICs. Notably, the lyophilized IBT-V02 formulation exhibited significant in vivo efficacy in various preclinical infection models against the S. aureus clinical isolates from LMICs, which was comparable to our liquid formulation. Collectively, our findings suggested that lyophilization is an effective alternative to liquid vaccine formulations of our IBT-V02 vaccine against S. aureus infections, which has important implications for protection from S. aureus isolates from LMICs.